Efektivitas Breathing Exercise Terhadap Penilaian Tingkat Kelelahan Pada Pasien Penyakit Jantung Koroner - Rahmad Wahyudi (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
Coronary Heart Disease (CHD)causes the coronary arteries to narrow and theconsumption of O2 to the tissues decreases sothat anaerobic metabolism produces lactic acidwhich causes fatigue as one of the effects orsymptoms of CHD. In the preliminary study,250 people experienced CHD with complaintsof fatigue of 125-150 people. The purpose ofthis study was to analyze differences in the levelof fatigue before and after breathing exercise incoronary heart disease patients in the ICUSYAMRABU Hospital Bangkalan. Method:This study uses an "Experimental" design withthe One Group Pre Test - Post Test designapproach. The variable of this study wasBreathing Exercise (independent variable) andthe level of fatigue in CHD patients (dependentvariable). Data was taken on the entirepopulation of CHD patients in the ICUSYAMRABU Bangkalan Hospital with anestimated 21 respondents with a total sample of20 respondents. Sampling technique usesaccidental sampling technique and datacollection using observation sheet with fatiquescale, The Results were analyzed using theWilcoxon Signed Rank Test with α (0.05). TheWilcoxon Signed Rank Test analysis showedthat there were differences in the level of fatiguebetween before and after breathing exercise inCHD patients in the ICU SYAMRABUBangkalan Hospital with significant results (ρ =0.002) <α (0.05). Health workers are expectedto be able to help CHD patients by creating anactivity program such as breathing exercise thatcan be introduced first through providingcounseling or direct giving to patients so thatpeople, families and patients with CHD knowand know about the picture of CHD, both fromsymptoms, the sign arrived at the stage of how